LaNi5.5 particles for reversible hydrogen storage in N-ethylcarbazole. (February 2021) - Yu, Hongen; Yang, Xue; Jiang, Xiaojing; Wu, Yiman; Chen, Shunpeng; Lin, Wei; Wu, Yong; Xie, Lei; Li, Xingguo; Zheng, Jie
Abstract: In this work, we demonstrate that the classic hydrogen storage alloy LaNi5 can catalyze the reversible hydrogen storage in N-ethylcarbazole (NEC), one of the most promising liquid organic hydrogen carriers (LOHCs), with high efficiency and cyclic stability. Using CaH2 reduction in molten salt, uniform LaNi5+x particles around 100 nm are obtained from hydroxide precursors. The sub-μm LaNi5.5 particles exhibit excellent catalytic ability for reversible hydrogen storage in NEC, which is originated from the synergism of surface excessive Ni and the LaNi5 core with reversible hydrogen storage property. Hydrogen storage capacity above 5.5 wt% H2 (based on 12 H-NEC) can be achieved for 9 cycles using 10 wt% LaNi5.5 . The time required to reach 5.5 wt% hydrogen storage capacity is about 4.5 h for NEC hydrogenation at 453 K and 4.0 h for 12 H-NEC dehydrogenation at 473 K. The results are very promising in developing high-efficiency LOHC-based hydrogen storage systems and provide new insights into hydride-based catalysts. Graphical Abstract: ga1 Highlights: Successfully synthesized uniform, 100 nm classic hydrogen storage alloy LaNi5. Efficient two-direction catalyst for reversible hydrogen storage in liquid organic hydrogen carrier N-ethylcarbazole. Excellent activity comes from built-in metal hydride/transition metal interface.